A Study of Membrane Impact on Spatial Resolution of Liquid In Situ Transmission Electron Microscope. (February 2020) - Li, Ming; Knibbe, Ruth
Abstract: Microchip technology with electron transparent membranes is a key component for in situ liquid transmission electron microscope (TEM) characterization. The membranes can significantly influence the TEM imaging spatial resolution, not only due to introducing additional material layers but also due to the associated bulging. The membrane bulging is largely defined by the membrane materials, thickness, and short dimension. The impact of the membrane on the spatial resolution, especially the extent of its bulging, was systematically investigated through the impact on the signal-to-noise ratio, chromatic aberration, and beam broadening. The optimization of the membrane parameters is the key component when designing the in situ TEM liquid cell. The optimal membrane thickness of 50 nm was found which balances the impact of membrane bulging and membrane thickness. Beyond this, the short membrane window dimension and the chip nominal spacing should be minimized. However, these two parameters have practical limitations in regards to chip handling.